WeChat as a Platform for Problem-Based Learning Among Hematological Postgraduates: Feasibility and Acceptability Study - Luo, Ping; Pang, Wenwen; Wang, Yingying; Liu, Minghui; Zhou, Shu; Liu, Shuai; Zhang, Xian; Liu, Li; Liu, Yanan; Zhou, Fuling (JMIR Publications, 2021)
BackgroundHematological medicine is a practical discipline that is difficult to study. Problem-based learning (PBL) is an innovative student-centered teaching method wherein students define their own learning objectives from clinically based problems. Considering that WeChat is the most popular communication app in China, we selected it as a new platform for online PBL to reduce the limitations of traditional PBL in hematology teaching. ObjectiveThis study aims to explore a new pedagogical method called WeChat-PBL, which is based on real micro clinical cases for postgraduates majoring in hematology and to demonstrate its feasibility and acceptability. MethodsA total of 48 hematological postgraduates and 7 tutors participated in this study. We divided the participants into 7 groups where students can learn theoretical knowledge. After each course, the members of each group were required to complete in-class quizzes. Moreover, the students and tutors were required to fill out periodic (after each class) and overall (after each semester) evaluations. ResultsA total of 8 micro clinical cases were presented in WeChat-PBL. The average quiz score for acute myelogenous leukemia, chronic myeloid leukemia, multiple myeloma, acute promyelocytic leukemia, and lymphoma were 89.0%, 86.0%, 83.4%, 88.8%, and 77.5%, respectively. Periodic evaluations showed that both students and tutors were satisfied with the process of WeChat-PBL. The overall evaluation results showed that WeChat-PBL was able to positively impact the learning experiences of hematological postgraduates. ConclusionsOur results indicate the feasibility and acceptability of the WeChat-PBL teaching method for postgraduates majoring in hematology.